STAGES OF CREATING A STRATEGIC MANAGEMENT PLAN OF THE COMPANY - Associate Professor U.A. Mukhammadiev; U.Ch. Khudoykulov (Zeta Repository, 2023)
This article focuses on such a complex issue as the formation of a company's strategic plan. The concepts of strategic planning, business planning and budgeting are considered. The necessity of communication between them is determined. A summary of these plans is given.